Strzał z dystansu. O Pierwszej piątce Stanisława Barańczaka - Hendrykowski, Marek (Przestrzenie Teorii, 2016)
Marek Hendrykowski’s article provides an analysis and interpretation of Barańczak’s well-known poem “Pierwsza piątka” [The First Five], whose main characters are the basketball legends of Boston Celtics, NBA champions on many occasions.